Supercapacitor Multi-layer Sealing Structure Combining Ionic Nanofiller-Interfacial Active Primer and Micro-Pattern Anchoring Structure and Method for Manufacturing the Same
Patent Information
- Application Number
- KR1020250194652
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-12-10
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-12-10
Smart Images

Figure 112025139270834-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to packaging technology for electrochemical energy storage devices, and more specifically, to a metal case sealing structure for a supercapacitor or electric double layer capacitor (EDLC) having high power output and long lifespan characteristics. More specifically, the invention relates to a supercapacitor multilayer sealing structure combining an ionic nanofiller-surface active primer and a micro-pattern anchoring structure, which can fundamentally prevent electrolyte leakage even in high temperature, high humidity, and thermal shock environments by applying a functional nanomaterial that physically and chemically maximizes the interfacial bonding force between a metal case, such as aluminum, and a sealing resin, and actively suppresses the penetration of electrolyte ions. Background Technology
[0002] In general, supercapacitors have lower energy density compared to secondary batteries such as lithium-ion batteries, but they have the advantages of being able to rapidly charge and discharge and having a semi-permanent lifespan, so they are widely used as power stabilization devices for renewable energy generation systems, auxiliary power sources for electric vehicles (EVs), and memory backup power sources for consumer electronics.
[0003] Conventional supercapacitors are manufactured by housing a device, in which a positive electrode, a negative electrode, and a separator are wound, into a cylindrical or rectangular aluminum case, injecting an electrolyte, and then sealing the opening of the case. In conventional technology, rubber gaskets or methods involving the injection and curing of polymer resins such as epoxy have been primarily used for this sealing.
[0004] For example, Korean Patent Publication No. 10-2019-0045666 (High-voltage supercapacitor and method for manufacturing the same) discloses a general manufacturing process in which a wound element is housed within an aluminum case, an electrolyte is injected, and the top is sealed. However, this conventional technology has the following structural limitations.
[0005] First, since the adhesion between the aluminum case surface and the organic sealant (rubber or epoxy) relies simply on mechanical jamming or weak secondary bonds, delamination easily occurs due to vibration or shock during long-term use.
[0006] Second, due to the significant difference in the coefficient of thermal expansion (CTE) between the metal case and the polymer sealant, continuous thermal stress is applied to the sealing interface caused by heat generation during the charging and discharging of the supercapacitor or external temperature changes (thermal cycling). This induces microcracks, which become leakage pathways for the electrolyte.
[0007] Third, organic electrolytes used in supercapacitors (e.g., acetonitrile, propylene carbonate, etc.) gradually diffuse into the polymer sealant and cause the polymer chains to swell, which is the main cause of the rapid decline in sealing performance by lowering the mechanical strength and glass transition temperature (Tg) of the sealant.
[0008] Therefore, there is an urgent need to develop a new level of sealing structure that can simultaneously secure physical anchoring, chemical crosslinking, and material chemical resistance, going beyond simply roughening the metal surface or using general silane coupling agents.
[0009] [Prior Art] [Patent Document 1] Republic of Korea Published Patent No. 10-2019-0045666 (Published May 2, 2019) The problem to be solved
[0011] The present invention has been devised to fundamentally solve the problems of the aforementioned prior art, and the technical problem that the present invention aims to achieve is as follows.
[0012] Implementation of physical / chemical hybrid bonding: By forming a micro-scale three-dimensional pattern on the surface of a metal case to provide a strong mechanical locking effect, and at the same time introducing a bifunctional surfactant primer to form a strong chemical cross-linking bond between the metal and the resin, the resistance to interfacial delamination is dramatically improved.
[0013] Ensuring thermomechanical durability: By dispersing functional nanofillers within the sealing resin matrix to increase the fracture toughness of the resin and controlling the coefficient of thermal expansion (CTE) to a level similar to that of metal, stress concentrated at the interface in thermal shock environments is alleviated and crack formation is suppressed.
[0014] Active electrolyte blocking (Ion Trapping): By introducing anionic functional groups onto the surface of nanofillers to induce electrostatic interactions (ion trapping) with electrolyte cations attempting to penetrate, it actively blocks swelling and degradation of physical properties caused by the electrolyte diffusing into the core of the sealant. means of solving the problem
[0016] The present invention provides the following means for solving the above problem.
[0017] In a multilayer sealing structure formed on the metal case surface of a supercapacitor,
[0018] A micro-pattern portion formed by etching or laser processing the surface of the metal case above;
[0019] A surfactant primer layer comprising a bifunctional compound formed on the surface of a metal case having the above-mentioned micro-pattern portion, the compound having a first functional group that binds to the metal and a second functional group that binds to the resin; and
[0020] ionic nanofiller reinforcing resin layer, which is laminated and cured on the above-mentioned surfactant primer layer and has surface-modified nanofillers dispersed within a polymer matrix; comprising
[0021] A supercapacitor multilayer sealing structure combining an ionic nanofiller-surface active primer and a micro-pattern anchoring structure is provided.
[0022] The above micro-pattern portion is characterized by having a depth and spacing in the range of 1 μm to 20 μm, and having a cross-sectional shape that is one of an inverted pyramid shape, a groove shape, or a rib shape.
[0023] The first functional group of the surfactant primer layer comprises a phosphate group (-PO4) or a carboxyl group (-COO) to form a coordination bond or a covalent bond with a metal ion on the surface of the metal case, and the second functional group comprises a silane group (-Si), an epoxy group, or an acrylic group to form a covalent bond with the ionic nanofiller reinforcing resin layer.
[0024] The above surfactant primer layer is characterized by being formed as a self-assembled monolayer (SAM).
[0025] The above nanofiller is a silica (SiO2) or alumina (Al2O3) particle, and on the surface of the nanofiller are sulfonic acid groups (-SO3 - ) or carboxyl group (-COO - It is characterized by having an anionic functional group including ) bonded thereto.
[0026] The polymer matrix of the above ionic nanofiller reinforcing resin layer is characterized by being composed of an epoxy resin or an acrylate-based resin.
[0027] The anionic functional groups on the surface of the nanofiller are characterized by being configured to bind with cations in the electrolyte through electrostatic attraction to inhibit the diffusion of the electrolyte into the polymer matrix.
[0028] The above ionic nanofiller reinforcing resin layer is characterized by reducing the difference in coefficient of thermal expansion (CTE) with the metal case and increasing fracture toughness through the dispersion of the nanofiller.
[0029] In a method for manufacturing a supercapacitor multilayer sealed structure,
[0030] A step of forming a micro-pattern portion by performing a laser processing or etching process on the surface of a sealing portion of a metal case;
[0031] A step of forming a surfactant primer layer by applying a difunctional material having both a metal-bonding functional group and a resin-bonding functional group to the surface on which the micro-pattern portion is formed; and
[0032] A method for manufacturing a supercapacitor multilayer sealing structure is provided, comprising the step of applying and curing a resin composition in which nanofillers surface-modified with anionic functional groups are dispersed on the above-mentioned surfactant primer layer to form an ionic nanofiller reinforcing resin layer.
[0033] A supercapacitor is provided that is characterized by having the above-described multilayer sealing structure to prevent leakage of the electrolyte. Effects of the invention
[0035] The 'supercapacitor multilayer sealing structure combining an ionic nanofiller-surface active primer and a micro-pattern anchoring structure' according to the present invention provides the following remarkable effects.
[0036] First, it provides a dramatic improvement in adhesive reliability. The physical anchoring effect in the vertical and horizontal directions caused by the micro-pattern and the chemical covalent / coordination bonding caused by the primer layer exert mutual synergy, increasing interfacial adhesion strength by several times compared to simple epoxy molding. This fundamentally prevents delamination of the sealing interface even in high temperature and high humidity environments.
[0037] Second, it ensures excellent thermo-mechanical stability. The resin layer reinforced with ionic nanofillers minimizes the difference in the coefficient of thermal expansion with the metal case and strengthens mechanical toughness, thereby dispersing stress concentration even in rapid thermal shock environments ranging from -40 to 85°C, which suppresses crack formation and gap formation.
[0038] Third, it possesses active resistance to electrolyte penetration. Anionic functional groups (-SO3 on the surface of the nanofiller) - , -COO - ) is a cation in the electrolyte (Li + , TEA + Electrochemically trapping (etc.) inhibits diffusion into the resin. This prevents swelling of the sealant and degradation of physical properties caused by the electrolyte, thereby enabling long-life operation of the supercapacitor without leakage.
[0039] Consequently, the present invention can significantly expand the scope of application of supercapacitors in advanced industrial fields requiring high reliability, such as electric vehicles (EVs), smart grids, and Internet of Things (IoT) sensors. Brief explanation of the drawing
[0041] FIG. 1 is a cross-sectional structure of a supercapacitor multilayer sealing structure according to the present invention. Specific details for implementing the invention
[0042] In order to clarify the understanding of the present invention in the following description, descriptions of known technologies regarding the features of the present invention will be omitted. The following embodiments are detailed descriptions to aid in understanding the present invention and are not intended to limit the scope of the rights of the present invention. Accordingly, equivalent inventions that perform the same function as the present invention will also fall within the scope of the rights of the present invention.
[0043] Furthermore, in the following description, identical identification symbols denote identical configurations, and unnecessary redundant descriptions and descriptions of known technologies are omitted. Additionally, descriptions of each embodiment of the present invention below that overlap with the description of the technology forming the background of the invention are also omitted.
[0044] The present invention provides the following means for solving the above problem.
[0045] A supercapacitor multilayer sealing structure combining an ionic nanofiller-surface active primer and a micro-pattern anchoring structure is provided, comprising: a micro-pattern portion formed by etching or laser processing the surface of the metal case of a supercapacitor; a surfactant primer layer formed on the surface of the metal case where the micro-pattern portion is formed, comprising a bifunctional compound having a first functional group that bonds to the metal and a second functional group that bonds to the resin; and an ionic nanofiller reinforcing resin layer laminated and cured on the surfactant primer layer, wherein a surface-modified nanofiller is dispersed within a polymer matrix.
[0046] The supercapacitor multilayer sealing structure according to the present invention was devised to overcome the limitations of conventional single polymer materials or simple physical bonding methods, and its technical gist is to establish a 3-tier defense system that integrates physical, chemical, and material stabilization technologies.
[0047] The multilayer sealing structure of the present invention consists of three main core components. First, the micro-pattern formed on the surface of the metal case significantly increases the contact area with the resin and provides a mechanical interlocking effect.
[0048] Second, the surfactant primer layer acts as a molecular bridge that chemically and strongly connects the heterogeneous interface between the inorganic metal and the organic resin.
[0049] Third, the outermost ionic nanofiller reinforcing resin layer provides mechanical rigidity and simultaneously performs an ion trap function that actively blocks the penetration of electrolyte ions, thereby suppressing the degradation of physical properties and swelling of the sealant itself.
[0050] This organic bonding structure effectively blocks electrolyte leakage at the source, even in high temperature, high humidity, and long-term thermal cycle environments.
[0051] The above micro-pattern portion is characterized by having a depth and spacing in the range of 1 μm to 20 μm, and having a cross-sectional shape that is one of an inverted pyramid shape, a groove shape, or a rib shape.
[0052] In the present invention, the micro-pattern portion is precisely controlled to induce a structural anchoring effect, going beyond a simple increase in surface roughness. The micro-pattern portion is formed through femtosecond laser processing or a precision photolithography-based etching process, and its depth and spacing are limited to a range of 1 μm to 20 μm.
[0053] These numerical ranges are critical for simultaneously ensuring the wettability of the resin and the structural strength of the metal case. If the depth is less than 1 µm, the high-viscosity sealing resin may not be sufficiently anchored into the pattern, which can lead to reduced peel resistance; if it exceeds 20 µm, the thickness of the metal case becomes locally thin, which can lower mechanical strength or reduce processing efficiency.
[0054] In particular, forming the cross-sectional shape of the pattern into an inverted pyramid, groove, or rib shape induces a structural undercut effect. This acts as a mechanical locking interlock against vertical peeling stress and horizontal shear stress after resin curing, dramatically increasing adhesive strength.
[0055] The first functional group of the surfactant primer layer comprises a phosphate group (-PO4) or a carboxyl group (-COO) to form a coordination bond or a covalent bond with a metal ion on the surface of the metal case, and the second functional group comprises a silane group (-Si), an epoxy group, or an acrylic group to form a covalent bond with the ionic nanofiller reinforcing resin layer.
[0056] The above surfactant primer layer is characterized by being formed as a self-assembled monolayer (SAM).
[0057] The surfactant primer layer of the present invention is introduced to resolve chemical discontinuities between the metal surface and the resin layer. This layer comprises a bifunctional molecule, wherein a metal-affinity functional group, such as a phosphate group or a carboxyl group, is present at one end of the molecule.
[0058] These form strong coordination bonds or ionic covalent bonds with metal ions present in the oxide film on the surface of aluminum. Since the binding energy of these coordination bonds is significantly higher than that of simple hydrogen bonds or van der Waals forces, they ensure resistance to hydrolysis in high-temperature and high-humidity environments.
[0059] At the same time, organic functional groups such as silane, epoxy, or acrylic groups are present at the other end of the molecule to form covalent cross-linking through a chemical reaction with the monomer of the resin applied on top.
[0060] As a result, a continuous chemical bond network without interruption is formed from the metal surface to the interior of the resin. In addition, it is preferable that the primer layer be formed in the form of a self-assembled monolayer (SAM).
[0061] This is intended to minimize the interface thickness to the nanometer level to prevent the primer layer itself from becoming a structural weak boundary layer, and to secure a uniform and dense bonding density along the irregularities of the metal surface.
[0062] The above nanofiller is a silica (SiO2) or alumina (Al2O3) particle, and on the surface of the nanofiller are sulfonic acid groups (-SO3 - ) or carboxyl group (-COO - It is characterized by having an anionic functional group including ) bonded thereto.
[0063] The polymer matrix of the above ionic nanofiller reinforcing resin layer is characterized by being composed of an epoxy resin or an acrylate-based resin.
[0064] The sealing resin layer of the present invention has a composite structure in which surface-modified nanofillers are dispersed within an epoxy or acrylate-based polymer matrix.
[0065] Silica or alumina particles with excellent chemical stability and insulation properties are used as the base for nanofillers.
[0066] A key technical feature is that anionic functional groups, such as sulfonic acid groups or carboxyl groups, are introduced at high density on the surface of the nanofiller. This is an essential component for providing active ion trapping functions, which will be described later, beyond simple mechanical reinforcement.
[0067] The anionic functional groups on the surface of the nanofiller are characterized by being configured to bind with cations in the electrolyte through electrostatic attraction to inhibit the diffusion of the electrolyte into the polymer matrix.
[0068] While conventional sealing materials defend against electrolyte penetration solely through a physical barrier, the present invention includes an active defense mechanism utilizing electrochemical principles. Cations such as lithium ions or quaternary ammonium ions contained in the organic electrolyte inside the supercapacitor penetrate between polymer chains and are the primary cause of swelling.
[0069] The anionic functional groups on the surface of the nanofiller introduced in the present invention form a strong electrostatic attraction with the electrolyte cation attempting to penetrate. This interaction traps and fixes the electrolyte cation on the filler surface, thereby drastically reducing the ion mobility. This significantly slows down the rate of electrolyte diffusion into the resin layer and suppresses the swelling of polymer chains, thereby ensuring long-term sealing reliability.
[0070] The above ionic nanofiller reinforcing resin layer is characterized by reducing the difference in coefficient of thermal expansion (CTE) with the metal case and increasing fracture toughness through the dispersion of the nanofiller.
[0071] The ionic nanofiller reinforcing resin layer of the present invention also dramatically improves thermo-mechanical durability. Generally, organic polymer resins have a very high coefficient of thermal expansion (CTE) compared to metal cases, causing severe thermal stress at the interface in a thermal cycling environment.
[0072] In the present invention, the difference in CTE with metal is mitigated by lowering the CTE of the entire resin composite through the uniform dispersion of inorganic nanofillers having a low CTE within the matrix. Additionally, the nanofillers increase the fracture toughness of the resin by bypassing the propagation path of micro-cracks that may occur due to external impact or thermal stress (Crack Deflection) or by dispersing stress at the crack tips. This acts as a decisive factor in suppressing crack initiation and interfacial delamination even under harsh temperature change conditions ranging from -40°C to 85°C.
[0073] A method for manufacturing a supercapacitor multilayer sealing structure comprises: a step of forming a micro-pattern portion by performing a laser processing or etching process on the surface of a sealing portion of a metal case; a step of forming a surfactant primer layer by applying a difunctional material having both a metal-bonding functional group and a resin-bonding functional group to the surface on which the micro-pattern portion is formed; and a step of forming an ionic nanofiller reinforcing resin layer by applying and curing a resin composition in which a nanofiller surface-modified with an anionic functional group is dispersed on the surfactant primer layer.
[0074] A supercapacitor is provided that is characterized by having the above-described multilayer sealing structure to prevent leakage of the electrolyte.
[0075] The method for manufacturing a multilayer sealing structure according to the present invention proceeds in sequential steps of (a) securing anchoring sites through surface processing, (b) chemical activation through the application of a primer, and (c) realizing final physical properties through the application and curing of a functional resin. Each step is organically interconnected and designed to minimize interfacial defects.
[0076] Supercapacitors equipped with a multilayer sealed structure completed through this manufacturing process (EDLC or hybrid supercapacitors) fundamentally solve the problem of electrolyte leakage, thereby maintaining high energy density and extending lifespan.
[0077] Therefore, it can be widely applied to industrial fields requiring high reliability, such as electronic components and renewable energy storage devices.
[0078] (Experimental Examples and Evaluation)
[0079] To demonstrate the superiority of the 'multilayer sealing structure combining an ionic nanofiller-surfactant primer and a micro-pattern anchoring structure' according to the present invention, an example of the present invention and a comparative example according to the prior art were prepared, and their mechanical adhesion strength, electrolyte resistance, and thermal shock reliability were evaluated.
[0080] - Example 1 (The present invention)
[0081] A micro pattern having an inverted pyramid shape with a depth of 10 μm and a spacing of 10 μm was formed on the surface of an aluminum (Al) case for a supercapacitor using a femtosecond laser. Subsequently, a surfactant primer layer in the form of a self-assembled monolayer (SAM) was formed by coating a difunctional molecule containing phosphate and silane groups at both ends diluted in an ethanol solvent.
[0082] Finally, a composition in which 5 parts by weight of silica nanofillers with sulfonic acid groups introduced to the surface were dispersed in 100 parts by weight of an epoxy resin matrix was applied onto the primer layer and cured at 150°C for 2 hours to complete the multilayer sealing structure.
[0083] - Comparative Example 1 (Prior Art)
[0084] After imparting surface roughness to the aluminum case surface through conventional sandblasting, a standard epoxy sealant was applied and cured without separate primer treatment or the addition of nanofillers.
[0085] - Comparative Example 2 (Partial Application)
[0086] A micro pattern was formed in the same manner as in Example 1, but the surfactant primer layer was omitted and a general epoxy sealant (without nanofillers) was applied and cured.
[0087] Lap Shear Strength Evaluation: Initial adhesive strength was measured in accordance with ASTM D1002 standards, and the weather resistance of the interface was evaluated by measuring the strength retention rate after exposure to a high temperature and high humidity environment (85℃, 85% RH) for 1,000 hours.
[0088] (2) Evaluation of electrolyte swelling resistance: After impregnating the specimen with a 1M TEA-BF4 / PC (propylene carbonate) electrolyte solution at 60°C for 500 hours, the depth of electrolyte penetration was measured through the weight change rate of the sealant and cross-sectional SEM analysis.
[0089] (3) Thermal Shock Life Evaluation: One cycle was defined as maintaining -40℃ and 85℃ for 30 minutes each, and the occurrence of leakage due to rapid temperature changes was checked using litmus paper.
[0090] division Initial adhesive strength (MPa) 85 / 85 Strength after 1000hr (MPa) Strength retention rate (%) note Comparative Example 1 6.5 1.2 18.5% Interfacial delamination occurs Comparative Example 2 12.4 5.8 46.8% Partial peeling occurs Examples 28.7 26.4 92.0% Cohesive Failure
[0092] As can be seen in [Table 1] above, the conventional technology Comparative Example 1 not only had low initial strength but also experienced a rapid decrease in adhesive strength of more than 80% due to moisture penetration in a high temperature and high humidity environment, and interfacial delamination occurred.
[0093] On the other hand, in Example 1 of the present invention, the mechanical locking effect caused by the micro-pattern and the chemical cross-linking bonding by the primer created synergy, resulting in an initial strength that was improved by approximately 4.4 times (28.7 MPa) compared to Comparative Example 1. In particular, it showed a high strength retention rate of 92% even after exposure to a harsh environment, and the failure mode also exhibited cohesive failure behavior in which the resin itself tears rather than the interface, proving that the interfacial bonding force is stronger than the cohesive force of the resin.
[0094] division Weight Change Rate (Swelling Ratio, %) Ion penetration depth (μm) Observation of surface condition Comparative Example 1 4.82 % Full Penetration Surface softening and microcracks Examples 0.35 % < 50㎛ (surface limited) No change
[0096] Comparative Examples 1 and 2 are organic solvents and cations (TEA) of the electrolyte. +) diffused into the polymer chain, causing a weight increase (swelling) of more than 4%. This lowers the Tg (glass transition temperature) of the sealant and causes a decrease in mechanical properties.
[0097] In contrast, Example 1 showed an extremely low weight change rate of 0.35%. This is due to the anionic functional groups (-SO3) on the surface of the nanofillers dispersed in the resin. - This is because it actively blocked diffusion into the resin core by trapping electrolyte cations through electrostatic attraction (Ion Trapping).
[0098] division 500 Cycle 1,000 Cycle 2,000 Cycle 3,000 Cycle Comparative Example 1 2 / 10 (leakage / number of samples) 8 / 10 10 / 10 (All damaged) - Comparative Example 2 0 / 10 3 / 10 7 / 10 - Examples 0 / 10 0 / 10 0 / 10 0 / 10 (All in good condition)
[0100] As a result of the thermal shock test, leakage occurred in most samples of Comparative Example 1 within 1,000 cycles due to stress concentration caused by the difference in the coefficient of thermal expansion (CTE) between the metal and the epoxy. However, no leakage occurred in Example 1 up to 3,000 cycles. This is because the nanofiller not only relieved thermal stress by controlling the CTE of the resin matrix but also improved fracture toughness, thereby suppressing crack initiation and propagation.
[0101] Synthesizing the experimental results above, it can be confirmed that the multilayer sealing structure according to the present invention provides significantly improved sealing reliability and durability compared to conventional technology by organically combining three mechanisms: 1) physical anchoring by a micro-pattern, 2) chemical crosslinking by a primer, and 3) electrolyte blocking and physical property reinforcement by an ionic nanofiller.
[0102] (Experimental Example 2)
[0103] In this invention, the following experiment was conducted to demonstrate that the depth and spacing of the micro-pattern are not merely design choices, but rather a critical numerical range for simultaneously solving two conflicting technical challenges: the impregnation of the sealant and the structural integrity of the case.
[0104] Micro-patterns in the shape of an inverted pyramid with various depths and pitches were formed on the surface of the seal of an aluminum case (thickness 0.5 mm) for a supercapacitor by stepwise adjusting the output of a femtosecond laser.
[0105] The control group and the experimental group (Example) were manufactured under identical conditions, except for the dimensions of the pattern. As the sealant, an 'epoxy resin reinforced with ionic nanofillers' having the same composition as Example 1 of the present invention was used, and the viscosity was fixed at approximately 3,000 cps at 25°C.
[0106] For each specimen, after resin application and curing, the 'resin impregnation rate (%)'—the percentage of the pattern filled without voids by resin—was measured through cross-sectional analysis using a scanning electron microscope (SEM), and the 'shear adhesive strength (MPa)' was measured according to ASTM D1002 standards.
[0107] In addition, to verify the effect of pattern processing on the reduction in the strength of the case itself, the 'tensile strength retention rate (%)' of the specimen after processing was evaluated relative to the raw material before processing.
[0108] division Pattern depth / spacing (μm) Resin impregnation rate (%) Shear adhesive strength (MPa) Case Strength Retention Rate (%) note Comparative Example 2-1 0.1 15.4 6.8 99.8 Adhesion defect Comparative Example 2-2 0.5 42.1 11.5 99.5 Adhesion defect Example 2-1 1.0 94.5 22.4 99.2 critical point (lower limit) Example 2-2 5.0 98.8 26.8 98.5 excellence Examples 2-3 10.0 99.9 28.7 97.1 very best Examples 2-4 20.0 100.0 29.1 91.5 Critical point (upper limit) Comparative Example 2-3 30.0 100.0 29.2 76.4 Base material damage Comparative Example 2-4 50.0 100.0 24.5 62.8 severe damage
[0109] From the above experimental results, it was confirmed that excellent adhesion and case durability can be simultaneously secured only within the range of 1 to 20 μm specified in the present invention, and the specific analysis details are as follows.
[0110] In the case of Comparative Examples 2-1 (0.1 μm) and 2-2 (0.5 μm), the resin impregnation rate was found to be significantly lower than 50% as the pattern depth approached the nanoscale. This was because the resin could not penetrate into the micro-pattern due to the viscosity and surface tension of the sealing resin and became blocked at the entrance. As a result, a large number of micro-voids were formed inside the pattern, reducing the adhesion area and acting as interfacial defects.
[0111] On the other hand, an inflection point was observed where the resin impregnation rate rapidly increased to 94.5% when the pattern depth reached 1.0 μm (Example 2-1). This is the effective depth at which capillary pressure overcomes viscous resistance and begins to draw the resin into the pattern, suggesting that the physical anchoring effect is substantially exerted only when a depth of 1 μm or more is secured.
[0112] As the pattern depth increased, the adhesive strength tended to increase, but serious adverse effects were observed in the range exceeding 20㎛. Looking at Comparative Examples 2-3 (30㎛) and 2-4 (50㎛), the adhesive strength was excellent, but the case strength retention rate dropped sharply to 76.4% and 62.8%, respectively.
[0113] This is because the effective cross-sectional area is reduced as an excessively deep pattern is formed on the surface of the thin metal case, and a stress concentration phenomenon, i.e., a notch effect, occurs in the valleys of the pattern. As a result of the analysis of the actual tensile fracture surface, in Comparative Examples 2-3 and above, fracture behavior was confirmed in which the aluminum substrate itself, rather than the adhesive interface, was torn along the pattern line.
[0114] On the other hand, in the case of 20 μm (Example 2-4), while exhibiting a perfect impregnation rate of 100% and maximum level of adhesion, the case strength retention rate was maintained at a compliant 90% or higher. In other words, 20 μm has technical significance as an upper limit that can maximize the anchoring effect without compromising structural soundness.
[0115] In summary, if the depth and spacing of the micro-pattern are less than 1 µm, adhesion failure occurs due to insufficient resin filling, and if they exceed 20 µm, the structural strength of the metal case is reduced, increasing the risk of breakage. Therefore, the numerical range of 1 to 20 µm has been proven to be the optimal critical range that simultaneously satisfies sealing performance to prevent electrolyte leakage and the structural safety of the energy storage device.
[0116] Although various embodiments of the present invention have been described above, these embodiments and the drawings attached to this specification merely clearly illustrate a part of the technical concept included in the present invention. It is obvious that variations and specific embodiments that can be easily deduced by a person skilled in the art within the scope of the technical concept included in the specification and drawings of the present invention are all included within the scope of the rights of the present invention.
Claims
Claim 1 A supercapacitor multilayer sealing structure combining an ionic nanofiller-surface active primer and a micro-pattern anchoring structure, comprising: a micro-pattern portion formed by etching or laser processing on the surface of a metal case of a supercapacitor; a surfactant primer layer formed on the surface of the metal case where the micro-pattern portion is formed, comprising a bifunctional compound having a first functional group that bonds to the metal and a second functional group that bonds to the resin; and an ionic nanofiller reinforcing resin layer laminated and cured on the surfactant primer layer, wherein a surface-modified nanofiller is dispersed within a polymer matrix. Claim 2 A supercapacitor multilayer sealing structure according to claim 1, characterized in that the first functional group of the surfactant primer layer comprises a phosphate group (-PO4) or a carboxyl group (-COO) to form a coordination bond or a covalent bond with a metal ion on the surface of the metal case, and the second functional group comprises a silane group (-Si), an epoxy group, or an acrylic group to form a covalent bond with the ionic nanofiller reinforcing resin layer. Claim 3 A method for manufacturing a supercapacitor multilayer sealing structure comprising: a step of forming a micro-pattern portion by performing a laser processing or etching process on the surface of a sealing portion of a metal case; a step of forming a surfactant primer layer by applying a difunctional material having both a metal-bonding functional group and a resin-bonding functional group to the surface on which the micro-pattern portion is formed; and a step of forming an ionic nanofiller reinforcing resin layer by applying and curing a resin composition in which a nanofiller surface-modified with an anionic functional group is dispersed on the surfactant primer layer.
Citation Information
Patent Citations
Sheet for cell case and cell device
KR100628581B1
Case
KR101469998B1
Outer material for storage device and storage device using the same
KR1020240072144A